Logística reversa de resíduos têxteis: um estudo de caso - CONCEIÇÃO, Monique Batista (004, 2022)
Com a produtividade nas indústrias têxteis, as questões ligadas a sustentabilidade se tornaram muito importantes no mercado e a logística reversa é uma aliada essencial para esse contexto. Por meio de estudos bibliográficos esse trabalho vai apresentar a história da indústria têxtil no brasil, os processos produtivos em uma tecelagem onde acaba gerando alguns resíduos sólidos, e por um estudo de caso, pretende apresentar quais são os destinos destes, visando entender a logística reversa através da venda desses materiais para uma empresa de comércio atacadista de resíduos sólidos. Com o auxílio de dados quantitativos e qualitativos da geração de resíduos no setor, são apresentados quais os impactos sociais, ambientais e econômicos que esses materiais causariam se não houve essa gestão de coleta, armazenagem e destinação correta.

With the productivity in the textile industries, issues related to sustainability have become very important in the market and reverse logistics is an essential ally in this context. Through bibliographic studies this study will present the history of the textile industry in Brazil, the production processes in a weaving factory where it ends up generating some solid waste, and through a case study, it intends to present what are the destinations of these, aiming to understand the reverse logistics by selling these materials to a solid waste wholesaler. By means of bibliographic studies this work will present the history of the textile industry in Brazil, the production processes in a weaving factory where it ends up generating some solid waste, and through a case study, it intends to present what are the destinations of these, aiming to understand the reverse logistics by selling these materials to a solid waste wholesaler. With the aid of quantitative and qualitative data on the generation of waste in the sector, are presented which social, environmental and economic impacts that these materials would cause if there was not this management of collection, storage and correct destination.
Reverse logistics of textile waste: a case study
Keywords: Indústria têxtil; Sustentabilidade; Logística reversa; Resíduos industriais (reciclagem); Gestão e Negócios